Gastric high-grade dysplasia can be associated with submucosal invasion: Evaluation of its prevalence in a series of 121 endoscopically resected specimens - Sakurai, Urara; Lauwers, Gregory Y.; Vieth, Michael; Sawabe, Motoji; Arai, Tomio; Yoshida, Tatsuya; Aida, Junko; Takubo, Kaiyo (American Journal of Surgical Pathology, 2014)
Gastric neoplasms classified as high-grade dysplasia (HGD) by Western pathologists are frequently diagnosed as tubular adenocarcinoma in Japan. Here, we evaluated the prevalence of submucosal and lymphovascular invasion in a series of 125 endoscopically resected gastric neoplasms. On the basis of Western criteria, the lesions were classified as poorly cohesive carcinomas (n=4) (excluded from further analysis), low-grade dysplasia (n=4), pure HGD (n=78), HGD with tubular adenocarcinoma (n=4), and pure tubular adenocarcinoma (n=35). Submucosal invasion was found in 3.8% of the 78 HGDs, 75.0% of the 4 HGDs combined with adenocarcinoma, and 11.4% of the 35 adenocarcinomas. Venous invasion was detected in 1.3% of the 78 HGDs, 75% of the 4 HGDs combined with adenocarcinoma, and none of the 35 tubular adenocarcinomas. Lymphatic invasion was absent in HGD but noted in 25% of the HGDs combined with adenocarcinoma, and 2.9% of the tubular adenocarcinomas. Thus, we demonstrated that lesions characterized as HGD on the basis of Western criteria can be associated with submucosal and lymphovascular invasion. Endoscopic therapy has made it less crucial to differentiate between HGD and intramucosal adenocarcinoma in biopsy samples of small tubular neoplasms. However, it is important to recognize that the criteria for dysplasia currently used in the West may understate the degree of malignant potential. To limit any diagnostic discrepancy between biopsy, endoscopic resection, and surgical specimens, it is suggested that the features of HGD and adenocarcinoma be reevaluated, which may result in some lesions being classified as mucosal adenocarcinoma.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Endoscopic resection; Gastric dysplasia; Gastric neoplasm; Intramucosal adenocarcinoma